Mitral annular disjunction: A systematic review of the literature. Issue 8 (5th August 2019) - Bennett, Sadie; Thamman, Ritu; Griffiths, Timothy; Oxley, Cheryl; Khan, Jamal Nasir; Phan, Thanh; Patwala, Ashish; Heatlie, Grant; Kwok, Chun Shing
Abstract: Background: Mitral annular disjunction (MAD) is a structural abnormality where there is a separation between the mitral valve annulus and the left atrial wall which is not well understood. Methods: We conducted a systematic review to evaluate the prevalence of MAD, factors associated with MAD and clinical outcomes among patients with MAD. Results: A total of 19 studies were included in this review, and the number of noncase report studies had between 23 and 1439 patients. The pooled rate of MAD in studies of myxomatous mitral valve patients was 66/130 (50.8%, 3 studies), and among patients with mitral valve prolapse was 95/291 (32.6%, 3 studies). One study suggests that 78% of patients with MAD had mitral valve prolapse, and another suggested it was strongly associated with myxomatous mitral valve disease (HR 5.04 95% CI 1.66–15.31). In terms of clinical significance, it has been reported that MAD with disjunction > 8.5 mm was associated with nonsustained ventricular tachycardia (OR 10 95% CI 1.28–78.1). There is also evidence that gadolinium enhancement in papillary muscle (OR 4.09 95% CI 1.28–13.05) and longitudinal MAD distance in posterolateral wall (OR 1.16 95% CI 1.02–1.33) was predictive of ventricular arrhythmia and late gadolinium enhancement in anterolateral papillary muscle was strongly associated with serious arrhythmic event (OR 7.35 95% CI 1.15–47.02). Conclusions: Mitral annular disjunction appears to be common in myxomatous mitral valve disease and mitral valve prolapse which can be detected on cardiac imaging and may be important because of its association with ventricular arrhythmias and sudden cardiac death.